Environmental and Occupational Lead Exposure Among Children in Cairo, Egypt: A Community-Based Cross-Sectional Study. Issue 9 (March 2016) - Moawad, Eman Mohamed Ibraheim; Badawy, Nashwa Mostafa; Manawill, Marie
Abstract : Abstract: The aim of this study was to assess childhood lead exposure in a representative sample of Cairo, and to investigate the possible risk factors and sources of exposure. This cross-sectional study was conducted from November 2014 through April 2015. The target population was children aged 6 to 18 years, recruited into 4 groups, garbage city, moderate-living standard area, urban and suburban schools, and workshops in the city of Cairo. Blood lead levels (BLLs) and hemoglobin (Hb) concentrations were measured. Also, potential local environmental sources were assessed for hazardous lead contamination. Analysis on 400 participants has been carried out. A total of 113 children had BLLs in the range 10 to 20 μg/dL. Smoking fathers, housing conditions, playing outdoors, and exposure to lead in residential areas were significantly correlated with high BLLs. The mean values of hemoglobin were inversely correlated with BLLs. Children involved in pottery workshops had the highest BLLs and the lowest Hb values with a mean of (43.3 μg/dL and 8.6 g/dL, respectively). The mean value of environmental lead in workshop areas exceeded the recommended levels. Also, those values measured in dust and paint samples of garbage city were significantly high. Moreover, the mean lead levels in the soil samples were significantly higher in urban schools ( P = 0.03) than the suburban ones. Childhood lead poisoning accounts for a substantial burden in Egypt, which could be preventable. Development of national prevention programs including universal screening program should be designed to reduce incidence of lead toxicity among children.